The Brain and Movement: How Physical Activity Affects the Brain - Andrea De Giorgio; Goran Kuvacic; Mirjana Milic; Johnny Padulo (Montenegrin Sports Academy, 2018)
improvement of cardiovascular effi cacy to the enhancement of muscular functions, metabolic balance, and organ systems. Th e brain is no exception and benefi ts greatly from movement, both structurally and functionally. Memory, creativity, and intelligence, are only a few of the many things that are regulated by the brain. Th e literature demonstrates the benefi ts of physical activity on numerous factors that infl uence brain functions. Th e present short review aims to clarify how physical activity aff ects the human brain. We have identifi ed the infl uence of movement on the brain, through investigation of this infl uence according to the close relation of physical activity with cognitive processes and brain development. Th ese fi ndings off er an insight into several conclusions regarding the infl uence of movement on the brain, which is soundly based on relevant literature.